Access, diversity, equity and inclusion in cultural organizations : insights from the careers of executive opera managers of color in the U.S. - Cuyler, Antonio C. (Antonio Christopher), 1978- (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"Low ticket sales, an aging audience, a shrinking donor base, rising costs - opera is in crisis. Moreover, there is a stifling lack of diversity among opera executives with over 90% of US opera's executives identifying as White. Opera in Australia, Canada, and the U. K. reveals similar problems. What if an inability to recruit and retain diverse executives is a key source of opera's challenges? If more diverse opera executives existed would the art form overcome its struggle to appeal to contemporary society? Given that diversity is often the key to unlocking innovation, what solutions to opera's challenges might emerge from more diverse executives? This is the first research book to investigate the careers of diverse executives and identify factors that advanced or impeded their careers. By examining the barriers, opportunities, strategies and experiences in the careers of executive opera managers of color in the U. S., it interrogates the impact of social identities on arts managers' careers and explores how opera might attract and retain more diverse arts managers to ensure its future. It will also serve to inspire Arts Management students who may view their class, disability, ethnicity, gender, or sexual orientation as a liability in their pursuit of executive careers in Arts Management"--
Act I. Introduction -- Act II : Career Narratives. Henry Akina : From Stage Director to Artistic Director of Hawaii Opera Theatre ; Torrie Allen : From Singer to General/Artistic Director of Anchorage Opera ; Wayne Brown : From Orchestra Manager to President & CEO of Michigan Opera Theatre ; Michael Ching : From Composer to General/Artistic Director of Opera Memphis ; Linda Jackson : From Stage Manager to Managing Director of Connecticut Opera ; Maestro Willie Anthony Waters : From Conductor to General Artistic Director of Connecticut Opera -- Act III. Finale.
OCLC-licensed vendor bibliographic record.
Keywords: African American opera company executives -- United States -- Biography; Pacific Islander American opera company executives -- United States -- Biography; Opera company executives -- United States -- Biography; BUSINESS & ECONOMICS / Careers / General; BUSINESS & ECONOMICS / Leadership; BUSINESS & ECONOMICS / Nonprofit Organizations & Charities